2018
DOI: 10.1051/matecconf/201814706004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wage, age and experience to labor productivity in construction works in Kota Langsa, Aceh

Abstract: Abstract. Construction work, as well as other production process depends on how people work towards it. The success of the work is determined by labor productivity. Labor productivity is affected by many factors such as human factors, environment, labor condition, leadership, type of work, level of difficulty etc. This article will discuss how these aspects influence the value of labor productivity. We limit our research on wage, age and experience from 15 to 30 workers in the brick work. The research is held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, attaining greater leverage in achieving organizational objectives through the formation of an organizational culture that embodies all cultures in the organization where the interest of all concerns is taken care of, the firm can expect harmony, greater efficiency, and a high level of performance among all employees in the pursuit of its objectives (Shahzad, F. et al, 2014). The age factor is as crucial as a culture when it comes to achieving greater efficiency and productivity ( Van O., Jan and Lenny S., 2010;Chung J., et al, 2015;Von B., et al, 2016;Bukit, I, et al, 2018). The physical aspect of a worker when he ages in most cases recede and so with his performance however this is just a generalization some studies find no hard evidence of a credible relationship among age, pay, and productivity (Oursvan, J., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, attaining greater leverage in achieving organizational objectives through the formation of an organizational culture that embodies all cultures in the organization where the interest of all concerns is taken care of, the firm can expect harmony, greater efficiency, and a high level of performance among all employees in the pursuit of its objectives (Shahzad, F. et al, 2014). The age factor is as crucial as a culture when it comes to achieving greater efficiency and productivity ( Van O., Jan and Lenny S., 2010;Chung J., et al, 2015;Von B., et al, 2016;Bukit, I, et al, 2018). The physical aspect of a worker when he ages in most cases recede and so with his performance however this is just a generalization some studies find no hard evidence of a credible relationship among age, pay, and productivity (Oursvan, J., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The physical aspect of a worker when he ages in most cases recede and so with his performance however this is just a generalization some studies find no hard evidence of a credible relationship among age, pay, and productivity (Oursvan, J., 2010). It has also been found that age and experience are great contributors to increasing productivity (INM Bukit, 2018) and work experience is a great predictor of performance than age (Bruce A., et al, 1990). The age factor has no credible impact on performance and may have to bear only when there are not enough opportunities such as promotion which can decimate work commitments and motivation (Sparrow, P.,1986).…”
Section: Discussionmentioning
confidence: 99%
“…Six Sigma reduces variation, which in turn improve productivity, Lean focus in eliminating waste and process design, which in turn improve productivity [7]. However, a wide variety of factors are influencing productivity; these factors are interrelated and interconnected, it relates to management factors, technological advancement [8], wages [9], working conditions [10], leadership and innovation [11], emotional intelligent [12,13], and labor competences and skills [14].…”
Section: Indeed This Integration Between Lean Manufacturing and Sixmentioning
confidence: 99%